2024
DOI: 10.1021/acsnano.3c11908
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Multiple-Phonon Absorption Causes Efficient Anti-Stokes Photoluminescence in CsPbBr3 Nanocrystals

Zhuoming Zhang,
Sushrut Ghonge,
Yang Ding
et al.

Abstract: Lead halide perovskite nanocrystals, such as CsPbBr 3 , exhibit efficient photoluminescence (PL) up-conversion, also referred to as anti-Stokes photoluminescence (ASPL). This is a phenomenon where irradiating nanocrystals up to 100 meV below gap results in higher energy band edge emission. Most surprising is that ASPL efficiencies approach unity and involve single-photon interactions with multiple phonons. This is unexpected given the statistically disfavored nature of multiple-phonon absorption. Here, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…These trends further indicate the complex spectral dependence of quantum yield for ASPL. This data appears to be consistent with observations made by Zhang et al of decreases in the efficiency of up-conversion as excitation is detuned from the band edge of surface-deposited CsPbBr 3 NC samples . Additionally, the smooth exponential decay in ASPL suggests a continuum of sub-gap states, as opposed to a single discrete electronic state assisting in up-conversion.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…These trends further indicate the complex spectral dependence of quantum yield for ASPL. This data appears to be consistent with observations made by Zhang et al of decreases in the efficiency of up-conversion as excitation is detuned from the band edge of surface-deposited CsPbBr 3 NC samples . Additionally, the smooth exponential decay in ASPL suggests a continuum of sub-gap states, as opposed to a single discrete electronic state assisting in up-conversion.…”
Section: Resultssupporting
confidence: 91%
“… ,, However, when excitation is further red-shifted, the much smaller cross section for two-photon absorption becomes relatively significant, so that the power law for up-converted photoluminescence gains superlinear character. As reported by Grandados del Águila et al, and observed in studies in our laboratory (see Figure S4), two photon up-conversion starts to become significant when exciting between 150 and 200 meV below-gap. , When sub-gap excitation decreases in energy there is an exponential decrease in ASPL intensity (see Figure A). For excitation energy with small detuning, where two-photon process does not contribute, throughout the spectral region known as the Urbach tail, it is reasonable to expect that the spectral-dependent decrease in ASPL intensity may simply be proportional to the exponential decrease in absorbance.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…An aspect of lead halide perovskites that attracts extensive interest is the strong coupling between charge carriers and the crystal lattice. Several studies have argued that electron–phonon coupling in lead halide perovskites leads to the formation of small polarons, i.e., a composite quasi-particle consisting of a charge carrier and a local lattice distortion. Considering the Frölich interaction, which assigns electron–phonon coupling to Coulomb interactions between charge carriers and the lattice ions as the most important contribution, polaron formation was first interpreted in terms of displacements of the organic cations . Later work, however, highlighted the coupling of charge carriers with the inorganic sublattice and related polaron formation to distortions of the PbX 6 octahedra. ,, This interpretation accounts for the rapid, sub-picosecond polaron formation , and agrees with changes of the X-ray absorption spectrum after photoexcitation. , Interestingly, both time-resolved X-ray absorption spectra and several computational studies indicated a marked difference in localization between a large electron-polaron and a small hole-polaron. Moreover, it was argued that this distinction is preserved in an electron–hole pair or excitonthe typical unit formed by photoexcitationand this finding was related to the smaller-than-expected electron–hole recombination rate in lead halide perovskites …”
mentioning
confidence: 99%